IGT Pest Control Sdn. Bhd. / Mohd. Haidir Haron...[et al.] - Ab. Ghani, Khairul Hafizi; Ab. Hadi, Nik Firdaus; Amir Nordin, Mohd. Azlan; Hassan, Mohd. Sahidan (2007)
IGT Pest Control Sdn. Bhd is a company Pest Control Service to try to give our customer the best service and quality and ti provide harmony in community that lear to a healthy life. This business operates in No. 322, Jalan Kangar Baru, Taman Mutiara, 01000 Kangar, Perlis.